Current issues of protection of land rights in local government bodies - Kovalenko T. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose: the purpose of the article is to conduct an analysis of the features, forms and procedures for the protection of land rights in local self-government bodies, to identify legal defects in the specified area and to justify proposals aimed at guaranteeing the land rights of subjects of land legal relations in Ukraine. Methodology. The methodology includes a comprehensive analysis and generalization of the available scientific and theoretical material and the formulation of relevant conclusions and recommendations. During the research, such methods of scientific knowledge were used: comparative-legal, systemic-structural, analysis and synthesis, historical method.Results. In the process of research, it was established that the protection of land rights in local self-government bodies can be carried out in the following forms: consideration of citizens’ appeals and resolution of land disputes. In the science of land law and in practice, the role of local self-government bodies in the protection of land rights and the resolution of land disputes is not unequivocally assessed, because there are problems associated with the low efficiency of the procedures for the protection of land rights by local self-government bodies, in particular at the stage of implementation of their decisions in the land spores.Originality. In the course of the conducted research, it was found that the resolution of land disputes by local self-government bodies has the following features: an exhaustive list of land disputes that they are authorized to resolve; the decision of the local self-government body regarding a certain land dispute does not have prejudicial significance; to ensure the resolution of land disputes, local self-government bodies may form conciliation commissions, the decisions of which are not recognized as the actual decision of the local self-government body, however, the protocols of the conciliation commissions of local self-government bodies may be accepted as evidence in the process of judicial resolution of a land dispute. Practical significance. The results of the study can be used in the research field – for the further development of the problems of legislative regulation of the resolution of land disputes by local self-government bodies, as well as in the rule-making work – in the preparation of projects of normative legal acts aimed at improving the legislative regulation of the protection of land rights of land subjects legal relations in Ukraine.